Biophysical microenvironment and 3D culture physiological relevance - Asthana, Amish; Kisaalita, William S. (Drug discovery today, 2013)
Force and substrate physical property (pliability) is one of three well established microenvironmental factors (MEFs) that may contribute to the formation of physiologically more relevant constructs (or not) for cell-based high-throughput screening (HTS) in preclinical drug discovery. In 3D cultures, studies of the physiological relevance dependence on material pliability are inconclusive, raising questions regarding the need to design platforms with materials whose pliability lies within the physiological range. To provide more insight into this question, we examine the factors that may underlie the studies inconclusiveness and suggest the elimination of redundant physical cues, where applicable, to better control other MEFs, make it easier to incorporate 3D cultures into state of the art HTS instrumentation, and reduce screening costs per compound.